KHOMANANI: AN HIV AND AIDS COMMUNITY MOBILISATION PROGRAMME FOR RESOURCE-CONSTRAINED SETTINGS - Geyer, Stephan (Social work, 2014)
An overview of HIV and AIDS statistics indicates that there were 31.6 million people living with HIV in 2010, and that 68% of those people were from Sub-Saharan Africa (UNAIDS, 2011:07). In South Africa, one of the countries in Sub-Saharan Africa, HIV prevalence among people between the ages of 15 and 49 has stabilised at 17.8%, with the absolute number of people living with HIV (PLHIV) showing a steep increase of approximately 100 000 additional PLHIV each year. The number of people aged 15 and older living with HIV is estimated to be 5 300 000. These figures actually mean that one out of every six people with HIV in the world lives in South Africa (UNAIDS, 2011:21). The authors therefore postulate that these statistics encapsulate the devastation that HIV and AIDS is causing, particularly in South Africa, which arguably carries the heaviest HIV and AIDS burden in the world. Initially South Africa’s efforts to mitigate the impact of HIV and AIDS were characterised by programme designs which followed an inflexible biomedical approach that did not focus on the influence of socio-economic and structural factors in addressing the pandemic. This situation, among others, contributed to raise the country’s HIV infection growth rate to among the highest in the world (Kahn, 2006:4)